Impact of Drying Time and Temperature Variation on the Antioxidant Activity of Cat's Whiskers (Orthosiphon stamineus Benth) - Fahrauk Faramayuda; Akhirul Kahfi Syam; Chandra Putra Prasetyo; Farhan Farhan (Journal of Pharmascience, 2026)
Cat's whiskers (Orthosiphon stamineus Benth.) is an herbal plant known for its significant antioxidant activity, making it a valuable resource in traditional medicine. This study aims to investigate the effects of different drying temperatures and durations on the antioxidant activity of cat's whiskers using the DPPH (2,2-diphenyl-1-picrylhydrazyl) reagent. The research was conducted through a systematic analysis of drying temperatures of 40, 50, and 60°C over 1, 2, and 3 days, to establish a correlation between drying parameters and antioxidant activity. Statistical analysis using two-way ANOVA revealed that drying conditions significantly influenced antioxidant activity, whereas water content remained stable across all treatments. Based on the results, the optimal drying condition is 60°C for 1 day, which exhibited the highest antioxidant activity, with an IC50 of 13.62 μg/mL and a water content of 3.69%. This study advances scientific knowledge, particularly regarding the most effective drying methods for cat's whiskers to preserve the stability of the plant's bioactive compounds. Ultimately, these findings provide a scientific basis for developing standardized drying protocols to maximize the therapeutic benefits of cat's whiskers in health applications.